THE SIGNIFICANCE OF IMAGERIES AND DIMENSION OF TIME IN ELIOT'S "RHAPSODY ON A WINDY NIGHT" - G. M. Adhyanggono (Celt: A Journal of Culture, English Language Teaching & Literature, 2010)
It is undeniable that Rhapsody on A Windy Night is one of T.S. Eliot's most powerful poems. Its power lies in the use of elaborate and vivid imagery. Though to some critics, this poem seems far from pretty; however, it still implies its "uniqueness". And the uniqeness here is closely related to the relation between the imageries and the dimension of time used. Therefore, this study is intended to assess the kind of relationship between the elements and to what extend they signify the meaning of the poem.